Thermal fatigue behaviour of hot-work tool steels: heat check nucleation and growth. (17th June 2008) - Ebner, R.; Marsoner, S.; Siller, I.; Ecker, W.
Cyclic thermal loading causes thermal gradients near the loaded surfaces, which are responsible for the development of cyclic strains and mechanical stresses in the sample that subsequently cause accumulated damage. The stress state changes during thermal fatigue loading if plastic strains occur. Most relevant are the formation of tensile stresses, which favour crack nucleation and crack growth, but thermal softening and cyclic softening also play an important role. The combined effect of microstructure, mechanical and physical properties on the thermal fatigue behaviour was studied by testing hot-work tool steels using a testing facility based on a pulsed laser beam. The results indicate that purely martensitic microstructures have a better thermal fatigue resistance than mixed martenitic/bainitic microstructures. High strength seems to be especially beneficial in cases with lower fatigue loads owing to thermal cycling. Higher thermal conductivity plays a beneficial role regarding the thermal fatigue resistance.